The Persister Character of Clinical Isolates of Staphylococcus aureus Contributes to Faster Evolution to Resistance and Higher Survival in THP-1 Monocytes: A Study With Moxifloxacin - Nguyen, Tiep K.; Peyrusson, Frédéric; Dodémont, Magali; Pham, Nhung H.; Nguyen, Hoang A.; Tulkens, Paul M.; Van Bambeke, Françoise (Frontiers in Microbiology, 2020)
Staphylococcus aureus may cause relapsing infections. We previously showed that S. aureus SH1000 surviving intracellularly to bactericidal antibiotics are persisters. Here, we used 54 non-duplicate clinical isolates to assess links between persistence, resistance evolution, and intracellular survival, using moxifloxacin throughout as test bactericidal antibiotic. The relative persister fraction (RPF: percentage of inoculum surviving to 100xMIC moxifloxacin in stationary phase culture for each isolate relative to ATCC 25923) was determined to categorize isolates with low (≤ 10) or high (>10) RPF. Evolution to resistance (moxifloxacin MIC ≥0.5 mg/L) was triggered by serial passages at 0.5xMIC (with daily concentration readjustments). Intracellular moxifloxacin maximal efficacy (Emax) was determined by 24h concentration-response experiments (pharmacodynamic model [Hill-Langmuir]) with infected THP-1 monocytes exposed to moxifloxacin (0.01 to 100xMIC) after phagocytosis. Division of intracellular survivors was followed by green fluorescence protein dilution (FACS). Most (30/36) moxifloxacin-susceptible isolates showed low RPF but all moxifloxacin-resistant (n=18) isolates harbored high RPF. Evolution to resistance of susceptible isolates was faster for those with high vs. low RPF (with SOS response and topoisomerase-encoding genes overexpression). Intracellularly, moxifloxacin Emax was decreased (less negative) for isolates with high vs. low RPF, independently from resistance. Moxifloxacin intracellular survivors were non-dividing. The data demonstrate and quantitate persisters in clinical isolates of S. aureus, and show that this phenotype accelerates resistance evolution and is associated with intracellular survival in spite of high antibiotic concentrations. Isolates with high RPF may represent a possible cause of treatment failure not directly related to resistance in patients receiving active antibiotics.